2015
DOI: 10.1088/0741-3335/57/6/065007
|View full text |Cite
|
Sign up to set email alerts
|

Observation of beta-induced Alfvén Eigenmode in J-TEXT tokamak

Abstract: High-frequency oscillations have been frequently observed under the conditions of tearing modes and runaway electrons in J-TEXT Ohmic plasmas. It is found the frequencies of these oscillations range from 20 to 45 kHz, being consistent with the beta-induced Alfvén Eigenmodes (BAEs) with the same order of the low-frequency gap induced by finite beta effects and the coupling of the shear Alfvén wave with the compressional response of the plasma. The exciting conditions for BAEs are investigated, which indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
4
28
0
Order By: Relevance
“…Investigations of BAEs are abundant, since they are ubiquitous in tokamak plasmas. Experimentally, the BAE was discovered on DIII-D [11] during neutral beam heating, and then it was also reported in FTU [14], HL-2A [15,16], EAST [17], and J-TEXT [18,19]. There are also many theoretical investigations [4,[20][21][22][23] and numerical simulations [24][25][26][27][28][29] of BAE.…”
Section: Introductionmentioning
confidence: 93%
“…Investigations of BAEs are abundant, since they are ubiquitous in tokamak plasmas. Experimentally, the BAE was discovered on DIII-D [11] during neutral beam heating, and then it was also reported in FTU [14], HL-2A [15,16], EAST [17], and J-TEXT [18,19]. There are also many theoretical investigations [4,[20][21][22][23] and numerical simulations [24][25][26][27][28][29] of BAE.…”
Section: Introductionmentioning
confidence: 93%
“…The experimental results show that the BAEs are related not only to the population of the energetic electrons, but also to their energy and pitch angles. The BAEs excited by the static resonant magnetic perturbation have been found on JTEXT [13]. Recently, the double BAE pairs inter acting with tungsten impurities that induced m/n = 2/1 snake fluctuations are mapped out for the first time on EAST [14].…”
Section: Introductionmentioning
confidence: 97%
“…Thus, they would interact with each other strongly. Recently, some experiments [9][10][11][12][13][14][15][16] have shown that BAEs can be excited in the presence of magnetic islands. BAEs were observed during tearing modes in FTU [9], TEXTOR [10], HL-2A [11,12] and J-TEXT [13,17] Ohmic plasmas, EAST with lower hybrid wave plasmas, HL-2A [18] and TJ-II stellarator [15] with energetic ions plasmas.…”
Section: Introductionmentioning
confidence: 99%